Seismic Analysis Of Tall Multistorey Structure Considering Variable Column Condition Using ETABS : A Review - Sahu, Peeyush Kumar; Chaturvedi, Prof. Anita (International Journal of Scientific Research in Civil Engineering, 2023)
One important factor that affects the project’s or building’s economy is the distance between columns. Because of this relationship between column spacing and panel size, the cost of raw materials can vary in reinforced concrete buildings. When column spacing is smaller, panels are smaller, and when column spacing is larger, panels are larger. In this paper presenting review of literature related to analysis of structures using analysis tools.